On the accuracy of simplified methods for the analysis of isolated bridges. - Franchin, P.
To foster the use of seismic isolation in structures, existing guidelines strive to formulate design methods which are simple and accessible to non-specialized engineers. On the other hand, not all of the simplifying provisions adopted by the norms can be said to have been adequately tested to provide a consistent level of accuracy. The study attempts, in particular, to elucidate three aspects related to the methods of analysis for linear or linearized isolated bridges on which little or no advice can be found in the norms. The first one is about the way one has to account for the fact that damping matrices of isolated bridges are never of proportional type. The present study demonstrates, through a number of typical applications, that classical modal analysis, using real modes and the diagonal terms of the modal damping matrices, still provide a fully acceptable approximation. The second and third aspects are related to the use of linearization expressions extended to the analysis of hyperstatic bridges. Parametric analyses conducted in the study show that none of the formulas in current use gives satisfactory results for both the displacement and the force responses, a requirement for a reliable design of an isolated bridge. How to use the equivalent linear parameters, and in particular the isolators equivalent damping ratios, in the context of a modal analysis, is treated next. This problem is seldom if ever mentioned in the norms where at most a formula is given for constructing modal damping ratios based on the damping ratios of the isolators. A rational, approximate procedure is discussed in this paper, applicable to all types of structures with non-proportional damping, which in the case of bridges can be shown to reduce to the expression provided in the Japanese bridge design guidelines.
Keywords: Bridges; Isolation; Non-proportional damping; Linearization